Masked Translation Priming With Concreteness of Cross-Script Cognates in Visual Word Recognition by Chinese Learners of English: An ERP Study - Chen, Shifa; Fu, Tingting; Zhao, Minghui; Zhang, Yuqing; Peng, Yule; Yang, Lianrui; Gu, Xiaolan (Frontiers in Psychology, 2022)
Translation equivalents for cognates in different script systems share the same meaning and phonological similarity but are different orthographically. Event-related potentials were recorded during the visual recognition of cross-script cognates and noncognates together with concreteness factors while Chinese-English bilinguals performed a lexical decision task with the masked translation priming paradigm in Experiment 1 (forward translation: L1-L2) and Experiment 2 (backward translation: L2-L1). N400 effect was found to be closely related to priming effects of cross-script cognate status and concreteness in Experiment 1; and in Experiment 2, N150 and N400 effects were related to priming effects of cross-script cognate status and concreteness, and greater priming effects of cross-script cognate status in cognates than in noncognates for abstract words were found in the time window of 100-200ms. Meanwhile, the asymmetry of translation directions was observed in smaller priming effects in forward translation than in backward translation in the time window of 100-200ms for abstract cognates, and in larger priming effects in forward translation than in backward translation in the time window of 350-550ms for each type of words. We discussed the roles of phonological activation and concreteness effects in view of the function of N150 and N400 components as well as the relevant models, mainly the Distributed Feature Model and Bilingual Interactive Activation (BIA+) model.